Prevalence and risk factors of migraine and non-migraine headache in older people – results of the Heinz Nixdorf Recall study. (May 2021) - Schramm, Sara; Tenhagen, Isabell; Schmidt, Börge; Holle-Lee, Dagny; Naegel, Steffen; Katsarava, Zaza; Jöckel, Karl-Heinz; Moebus, Susanne
Background: The prevalence of migraine and non-migraine headache declines with age. Methods: Data from the third visit (2011–2015) of the population-based Heinz Nixdorf Recall study were analysed (n = 2038, 51% women, 65–86 years). Possible risk factors for headache activity (obesity, education, smoking, sports, alcohol, partnership status, living alone, having children, sleep quality, depression, hypertension, diabetes mellitus, stroke, coronary heart disease, medication), and headache symptoms were assessed. We estimated the lifetime prevalence and the prevalence of current active headache of migraine with and without aura, and non-migraine headache. The associations between possible risk factors and headache activity (active vs. inactive) were estimated by age and sex-adjusted odds ratios and 95% confidence intervals (OR [95% CI]) using multiple logistic regression. Results: The lifetime prevalence of migraine was 28.6% (n = 584). One hundred and ninety-two (9.4%) had still-active migraine, 168 (3.5%) had migraine with aura, and 416 (5.9%) had migraine without aura. One hundred and sixty-eight (8.2%) had "episodic infrequent migraine, 0–8 headache days/month", 10 (0.5%) had "episodic frequent migraine, 9–14 headache days/month", and five (0.2%) had "chronic migraine, ≥15 headache days/month". Overall, 10 (0.5%) had "chronic headache, any headache on ≥15 days/month". Female gender and younger age were the most important associated migraine risk factors. Depression (1.62 [1.06; 2.47]) and poor sleep (1.06 [1.00; 1.12]) were associated with migraine and headache activity in general. Antihypertensives were associated with headache remission (0.80 [0.64; 1.00]). Additionally, undertaking less sports (0.72 [0.51; 1.03]) was associated with higher migraine activity. Conclusions: Headaches and migraines are not rare in the older population. They are related to mood and sleep disturbance, and migraine even to less physical activity. Antihypertensives are related to headache remission.